Admission kidney function is a strong predictor for the response to nutritional support in patients at nutritional risk. Issue 5 (May 2021) - Bargetzi, Annika; Emmenegger, Nora; Wildisen, Simone; Nickler, Manuela; Bargetzi, Laura; Hersberger, Lara; Segerer, Stephan; Kaegi-Braun, Nina; Tribolet, Pascal; Gomes, Filomena; Hoess, Claus; Pavlicek, Vojtech; et al.
Summary: Background: Patients with chronic kidney disease (CKD) are at substantial risk of malnutrition, which negatively affects clinical outcomes. We investigated the association of kidney function assessed at hospital admission and effectiveness of nutritional support in hospitalized medical patients at risk of malnutrition. Methods: This is a secondary analysis of an investigator-initiated, randomized-controlled, Swiss multicenter trial (EFFORT) that compared individualised nutritional support with usual hospital food on clinical outcomes. We compared effects of nutritional support on mortality in subgroups of patients stratified according to kidney function at the time of hospital admission (estimated glomerular filtration rates [eGFR] <15, 15–29, 30–59, 60–89 and ≥ 90 ml/min/1.73 m 2 ). Results: We included 1943 of 2028 patients (96%) from the original trial with known admission creatinine levels. Admission eGFR was a strong predictor for the beneficial effects of nutritional support in regard to lowering of 30-day mortality. Patients with an eGFR <15, 15–29 and 30–59 had the strongest mortality benefit (odds ratios [95%CI] of 0.24 [0.05 to 1.25], 0.37 [0.14 to 0.95] and 0.39 [0.21 to 0.75], respectively), while patients with less severe impairment in kidney function had a less pronounced mortality benefits (p for interaction 0.001). A similar stepwise association of kidney function and response to nutritional support was found also for other secondary outcomes. Conclusion: In medical inpatients at nutritional risk, admission kidney function was a strong predictor for the response to nutritional therapy. Initial kidney function may help to individualize nutritional support in the future by identification of patients with most clinical benefit. Clinical trial registration: Registered under ClinicalTrials.gov Identifier no. NCT02517476.